THE EFFECTIVENESS OF TEAM GAMES TOURNAMENT (TGT) LEARNING MODEL TO IMPROVE MEMORY SKILL ON TEACHING VOCABULARY - RAMADHANI, WULAN; Meiga Ratih Tirtanawat; Chyntia Heru Woro Prastiwi (PT. Pustaka Cendekia Publisher, 2024)
This study presents the author's experiment on the effectiveness of the Teams Games Tournament (TGT) learning model. The purpose of this study is to improve children's memory skills in vocabulary learning in grade 4 elementary school children. The researchers used experimental quantitative methods. In this study, researchers used crossword puzzles as learning media in conjunction with the Team Games Tournament learning model. In this study, the researchers made a comparison between the pre-test and post-test scores, namely the lowest score was 36 and the lowest score of the post-test was 40. And the maximum value of the pre-test was at 84 with the maximum value during the post-test was 88, so it was said that the study was quite effective in improving children's memory in 4th grade English vocabulary lessons.